Synthesis of 1,5-Diaryl-1,4-pentadien-3-one Amidinohydrazone Hydrochloride Under Ultrasound Irradiation - Chao Du; Ji Tai Li (E-Journal of Chemistry, 2012)
Synthesis of 1,5-diaryl-1,4-pentadien-3-one amidinohydrazone hydrochloride via the condensation of 1,5-diaryl-1,4-pentadien-3-one and aminoguanidine hydrochloride catalyzed by hydrochloric acid was carried out in 80-94% yield at 35-37°C within 1.5 h under ultrasound irradiation. Compared to the classical method, the advantages of this method are milder conditions, shorter reaction time and higher yield.